The potential therapeutic role of extracellular vesicles in osteoarthritis - Zhuang, Yu; Jiang, Shengjie; Yuan, Changyong; Lin, Kaili (Frontiers in Bioengineering and Biotechnology, 2022)
Osteoarthritis (OA) is a worldwide and disabling disease, which cause severe pain and heavy socioeconomic burden. However, pharmacologic or surgical therapies cannot mitigate OA progression. Mesenchymal stem cells (MSCs) therapy has emerged as potential approach for OA treatment, while the immunogenicity and ethical audit of cell therapy are unavoidable. Compared with stem cell strategy, EVs induce less immunological rejection, and they are more stable for storage and in vivo application. MSC-EVs-based therapy possesses great potential in regulating inflammation and promoting cartilage matrix reconstruction in OA treatment. To enhance the therapeutic effect, delivery efficiency, tissue specificity and safety, EVs can be engineered via different modification strategies. Here, the application of MSC-EVs in OA treatment and the potential underlying mechanism were summarized. Moreover, EV modification strategies including indirect MSC modification and direct EV modification were reviewed.